IS/IT Investment Evaluation Practices, B2BEC Adoption, and IT Maturity in large Australian Organizations: Preliminary Findings - Lin, Chad (Australasian Chapter of the Association for Information Systems, 2005)
The issue of expected and actual benefits realized from IS/IT investments has generated a lot of debate in the IS literature amongst researchers and practitioners. This problem has become more complex as the nature of IS/IT investments and the benefits they can deliver has evolved over time has changed rapidly. This research study aims to establish current practices and norms in managing benefits and evaluation on IS/IT investments by large organizations in Australia. The results indicated relatively high usage of these methodologies by the responding organizations. However, these methodologies were generally not used widely and effectively within these large Australian organizations. The results also demonstrated that there was a significant positive relationship between the use of IEM/BRM methodologies and the degree of satisfaction with the adoption of B2BEC. Furthermore, there appeared to be a significant positive relationship between the adoption and wide use of the evaluation methodologies and the level of IT maturity of the responding organizations.